2014
DOI: 10.1016/j.neuropsychologia.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Verbal learning and memory in agenesis of the corpus callosum

Abstract: The role of interhemispheric interactions in the encoding, retention, and retrieval of verbal memory can be clarified by assessing individuals with complete or partial agenesis of the corpus callosum (AgCC), but who have normal intelligence. This study assessed verbal learning and memory in AgCC using the California Verbal Learning Test—Second Edition (CVLT-II). Twenty-six individuals with AgCC were compared to 24 matched controls on CVLT-II measures, as well as Donders’ four CVLT-II factors (i.e., Attention S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 59 publications
3
38
0
1
Order By: Relevance
“…The bilateral retrieval of the learnt information has been well known in verbal memory, working memory and perceptual memory for special sensations, in which the corpus callosum plays an important role (Hasegawa et al, 1999; Wong, 2000; Peltier et al, 2012; Pietrasanta et al, 2012; Treble et al, 2013; Erickson et al, 2014). The two issues need to be cleared for these reports.…”
Section: Discussionmentioning
confidence: 99%
“…The bilateral retrieval of the learnt information has been well known in verbal memory, working memory and perceptual memory for special sensations, in which the corpus callosum plays an important role (Hasegawa et al, 1999; Wong, 2000; Peltier et al, 2012; Pietrasanta et al, 2012; Treble et al, 2013; Erickson et al, 2014). The two issues need to be cleared for these reports.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that participants with agenesis of corpus callosum performed significantly below healthy controls in memory related cognitive tests, suggesting that the corpus callosum facilitates more efficient learning and recall for both verbal and visual information101213. For individuals with CC impairments, visual memory traces in the right hemisphere might be less accessible to the language dominant left hemisphere for verbal recall10. Reduced interaction between visual and verbal systems may also affect the richness of initial encoding for both visual and verbal tasks10.…”
mentioning
confidence: 99%
“…They display a typical pattern of neuropsychological and psychosocial deficits, which include impaired verbal learning and memory. 4,5 Several studies have indicated that the absence of callosal fibers during development might influence the maturational processes of other brain regions; this influence can lead, for example, to a reduction in cortical thickness in some brain regions. 6,7 Because the appearance and growth of callosal fibers coincide with the development of the human hippocampus, we hypothesized that ACC could, consequently, affect the proper formation of this structure, which is crucial for learning and memory functions.…”
mentioning
confidence: 99%